The effect of solar tower height on its energy output at Ma’an-Jordan - Saad S. Alrwashdeh (AIMS Energy, 2018)
The solar power tower is a concentrated solar energy application that uses a receiver to capture reflected sunlight from the mirror field. Solar energy is seen as one of the solutions to the problem of climate change as it is environmentally friendly. In this work, the production of energy from a solar tower in the Ma’an region of southern Jordan was studied using a simulation program of 3D-Energy. The dependency of the power output on the tower height is presented while showing that greater power production can be facilitated by optimizing the height of the tower.